PENGARUH SISTEM E - FILING DAN KEPATUHAN WAJIB PAJAK ORANG PRIBADI DALAM PENYAMPAIAN SPT TAHUNAN (STUDI KASUS PADA SATUAN ZIDAM I/BUKIT BARISAN) - TIA NOVIRA SUCIPTO (JURNAL ILMIAH MAKSITEK, 2022)
This study aims to obtain empirical evidence regarding the effect of: (1) the quality of the e-filing system on the compliance ofindividual taxpayers in submitting Annual Tax Returns, (2) the perception of the convenience of individual taxpayers on theimplementation of e-filing on the compliance of individual taxpayers in submission of Annual Tax Returns, (3) Security andConfidentiality of the e-filing system against individual taxpayer compliance in the submission of Annual Tax Returns (4)System Quality, Perception of Taxpayer convenience and the Confidentiality and Security of the E-filing System on individualtaxpayer compliance in submission of Annual Tax Returns. This study uses a sample of individual taxpayers who use e-filingto submit Annual Tax Returns, namely in the Zidam I/BB unit area. The sampling technique used in this study is ProbabilitySampling. Probability sampling is a sampling technique that provides equal opportunities for each element (member) of thepopulation to be selected as a member of the sample. Data collection techniques with the method of filling out thequestionnaire. The analytical method used in this research is multiple linear regression. The results of this study, namely theperception of the convenience of taxpayers on the implementation of e-filing have a significant effect on the compliance ofindividual taxpayers in submitting the Annual Tax Returns, and the security and confidentiality of the e-filing system haveasignificant effect on the compliance of individual taxpayers in submitting the Annual Tax Returns. On the other hand, thequality of the e-filing system has no effect on the compliance of individual taxpayers in submitting the Annual Tax Returns.However, simultaneously the Quality of the System, Perceived Ease of Taxpayers and the Confidentiality and Security of theE-filing System affect the Compliance of Individual Taxpayers in Submitting Annual Tax Returns.